Keberlanjutan Usaha dan Daya Saing Pasar Minuman Sarabba Kota Makassar di Masa Pandemi Covid-19 - Thamrin Tahir (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2022)
This study uses a qualitative method to determine the competitiveness of traditional sarabba drinkers in this pandemic era against business sustainability in the Cerekang River environment. By using data coding techniques in analyzing, we can interview directly openly. The results show that the competitiveness of traditional Sarabba beverage business actors is still lacking, but the lack of Sarabba business actors still greatly impacts business sustainability, by increasing consumer interest so that the Sarabba business can be more advanced than before.